Malignant tumours as a rare cause of recurrent thrombophlebitis of the great saphenous vein - Baier, P.-M.; König, N.; Stark, H. J. (Phlebologie, 2008)
We present two case reports concerning patients who had to undergone surgical treatment according tp the diagnosis of thrombophlebitis with insufficiency of the greater saphenous vein and putative encapsulated haematoma in the lower left leg area. During the operation we found tumours with urgent suspicion of malignancy. The histological examination revealed the diagnosis of mesenchymal chondrosarcoma and malignant peripheral nerve sheath tumour which are extremely malignant, but very rare neoplasmas with unfavourable prognosis. Conclusion: Since both types of tumours are often located below the knee, phlebotomists and vascular surgeons should take them into account as differential diagnosis.
Keywords: Thrombophlebitis; progressive swelling of the extremities; mesenchymal chondrosarcoma; malignant peripheral nerve sheath tumour